Powerlessness in Post-Merger Integration - Nabila Ramadhani; Dian Ekowati (Journal of Accounting and Finance Management, 2026)
This study aims to explore the role of powerlessness as a manifestation of alienation in employees in the post-merger digital retail sector. Using qualitative methods, data were collected through in-depth interviews with eight informants. The results show that powerlessness manifests through three domains: 1. top-down decision-making without employee negotiation space; 2. dependence on technology that imposes boundaries between professional and private spaces; and 3. bureaucracy that hinders work effectiveness and professional autonomy. The accumulation of this powerlessness encourages the emergence of a survival strategy in the form of withdrawal where employees remain present but are not emotionally connected. This study highlights the importance of a post-merger integration process that pays attention to employees' emotional and mental well-being to mitigate alienation.